2017
DOI: 10.1200/jco.2017.72.8030
|View full text |Cite|
|
Sign up to set email alerts
|

Second-Line Hormonal Therapy for Men With Chemotherapy-Naïve, Castration-Resistant Prostate Cancer: American Society of Clinical Oncology Provisional Clinical Opinion

Abstract: Purpose ASCO provisional clinical opinions (PCOs) offer direction to the ASCO membership after publication or presentation of potential practice-changing data. This PCO addresses second-line hormonal therapy for chemotherapy-naïve men with castration-resistant prostate cancer (CRPC) who range from being asymptomatic with only biochemical evidence of CRPC to having documented metastases but minimal symptoms. Clinical Context The treatment goal for CRPC is palliation. Despite resistance to initial androgen depri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
49
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 69 publications
(44 reference statements)
2
49
0
2
Order By: Relevance
“…However, for advanced PCa, hormonal deprivation therapy can temporarily inhibit tumor progression through the androgen receptor signaling pathway, but this function is only effective for approximately 2 years. Then, serum levels of prostate‐specific antibody (PSA) increase again rapidly, meeting the stage of castration‐resistant prostate cancer (CRPC), which is the leading cause of tumor‐specific death in PCa …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for advanced PCa, hormonal deprivation therapy can temporarily inhibit tumor progression through the androgen receptor signaling pathway, but this function is only effective for approximately 2 years. Then, serum levels of prostate‐specific antibody (PSA) increase again rapidly, meeting the stage of castration‐resistant prostate cancer (CRPC), which is the leading cause of tumor‐specific death in PCa …”
Section: Introductionmentioning
confidence: 99%
“…Then, serum levels of prostate-specific antibody (PSA) increase again rapidly, meeting the stage of castration-resistant prostate cancer (CRPC), which is the leading cause of tumor-specific death in PCa. [11][12][13][14] Tumor-infiltrating immune cells (TIICs) are essential components of the tumor microenvironment and can alter the immune status of the tumor. Several studies have demonstrated therapeutic strategies against tumors by targeting TIICs.…”
mentioning
confidence: 99%
“…Besides, overestimating the risks of T3N0M0 (9.6% of RCC patients) implied a higher disease burden with overtreatment of adjuvant therapy. [22][23][24] Evaluation of the efficacy and excessive treatment could be solved better if the future adjuvant therapy RCTs adopted the modified AJCC staging system and performed subgroup analysis accordingly. Collectively, our modified AJCC staging system may have some impact on the adjuvant therapy trials setting which is highly controversial according to recent trials.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment toxicity and baseline or acquired chemotherapy resistance represent the main risks for DOC-treated patients [3,7]. In the past few years, a large number of systemic therapies such as abiraterone acetate, enzalutamide and alpharadine has been approved for CRPC patients [6]. Two randomised prospective clinical studies demonstrated that the combination of DOC with Androgen deprivation therapy provides a substantial survival benefit also for hormone sensitive patients [8,9].…”
mentioning
confidence: 99%
“…Androgen deprivation therapy is the "gold standard" treatment for advanced PCa [4]. While an initial response to therapy is common, most of patients will later develop biochemical, radiographic, and/or symptomatic evidence of cancer progression despite castrate levels of testosterone [5,6]. Docetaxel (DOC) represents a standard first-line treatment in men with castrationresistant prostate cancer (CRPC) for more than a decade.…”
mentioning
confidence: 99%